27 The role of ligands of activatory receptor NKG2D in the immune-dependent pathogenesis and evolution of inflammatory bowel disease (IBD). (9th November 2020) - Sidahmed, Heba; Ravindran, Shilpa; Manjunath, Harshitha; Mifsud, William; Charles, Adrian; Ammar, Adham; Khan, Muhammad; Al-Kaabi, Saad; Akobeng, Anthony; Al-Mohannadi, Muneera; Elawad, Mamoun; Tomei, Sara; et al.
Abstract : Background: Long-term inflammation in IBD is mediated by several immune cells, including T lymphocytes and natural killer (NK) cells, through the engagement of NK group 2D (NKG2D) receptors. Allelic variations of NKG2D ligands (NKG2Dls, MICA/B, ULBP1-3) influence differential levels and localization of protein expression or the release of soluble isoforms. The affinity of interaction with NKG2D can be also affected, modulating the cytotoxic activity of the target cell. Evaluation of these molecular pathways and soluble ligands presents the potential use a clinical biomarker for patient outcomes. Methods: Gut tissue biopsies (left and right sides) and peripheral blood were collected from patients. 10 pediatric and 11 adult patients with IBD, 10 patients with gut malignancies and history of IBD were included in the study. Plasma form IBD patients and 10 healthy donors as controls, was used to quantify soluble NKG2DLs (sNKG2DLs) by ELISA (R&D Systems Duo Set). Nucleic acids were extracted from gut biopsies using the BioMasher II (Kimble) and All Prep DNA/RNA universal kit (Qiagen). Single nucleotide polymorphisms (SNPs, N=26) and relative gene expression of NKG2DL genes were conducted by qPCR using Taqman assays. Results: 9/11 adult patients had diagnosis of ulcerative colitis, compared to 3/10 pediatrics. 5/10 pediatrics had Crohn's disease and 2/10 unclassified IBD. A trend of prevalence of some allelic variants was detected for most of NKGD2Ls.In addition, mRNA encoding for NKG2DLs was detected commonly, although with heterogeneous quantifications, in all the tissues, including the retrospectively collected malignancies with history of IBD. Interestingly, the levels of sNKG2DLs were higher in pediatric (p<0.001) as compared to adult patients. No or low levels of sNKG2DLs were detectable in healthy donors. Moreover 3/5 patients with the highest level (700–1500 pg/ml) of sMICA had homozygosity at least in one of the rs1051792 or rs1051794 polymorphic site (GG allele variant MICA-129Val or MICA-250Val) that have been reported to be associated with soluble form of MICA. Conclusions: These results, although preliminary and further investigations are ongoing, suggest the relevance of NKG2D/NKG2DL pathway in the development and evolution of IBD. sNKG2DLs could be detected in most of patients, with different levels and highest concentrations in pediatric patients. In some cases, the presence of sNKG2DLs in the plasma could be associated with defined polymorphisms in genes encoding for these proteins. Ethics Approval: This study was approved by Sidra Medicine and Hamad Medical Corporation Ethics Boards; approval number 180402817 and MRC-02-18-096, respectively.